Stroking parameters in front crawl swimming and maximal lactate steady state speed - Dekerle, J.; Nesi, X.; Lefevre, S.; Sidney, M.; Huot-Marchand, F.; Pelayo, P. (International Journal of Sports Medicine, 2005)
In order to increase or maintain speed at sub-maximal intensities, well-trained swimmers have an increase in their stroke rate, thus a decrease in their stroke. The purposes of this study were i) to ascertain whether the maximal speed from which the stroke length decreases significantly (SSLdrop) corresponds to the maximal lactate steady state swimming speed (SMLSS), and ii) to examine the effect of the exercise duration on the stroking parameters above, below, and at SMLSS. Eleven male well-trained swimmers performed an all-out 400-m front crawl test to estimate maximal aerobic speed (MAS) and four sub-maximal 30-min tests (75, 80, 85, and 90 % MAS) to determine SMLSS and SSLdrop and to analyse the evolution of the stroking parameters throughout these tests. SMLSS (88.9 ± 3.3 % MAS) and SSLdrop (87.3 ± 4.5 % MAS) were not significantly different from each other (p = 0.41) and were highly correlated (r = 0.88; p < 0.001). Moreover, a slight stroke rate increase, and a stroke length decrease, were observed above SMLSS but were only significant for the 5 swimmers unable to maintain this speed for 30 min (p > 0.05). During the 30-min tests swum below and at SMLSS, a steady state of stroking parameters was statistically reported. Thus, SMLSS seems to represent not only a physiological transition threshold between heavy and severe sub-maximal intensities but also a biomechanical boundary beyond which the stroke length becomes compromised.